Exploration of Luteolin as Potential Anti-COVID-19 Agent: Molecular Docking, Molecular Dynamic Simulation, ADMET and DFT Analysis - Ansari, Waseem A.; Ahamad, Tanveer; Khan, Mohsin Ali; Khan, Zaw Ali; Khan, Mohammad Faheem (Letters in Drug Design & Discovery, 2022)
Background: Coronavirus disease-2019 (COVID-19) has recently emerged as a pandemic respiratory disease with mild to severe pneumonia symptoms. No clinical antiviral agent is available so far. However, several repurposing drugs and vaccines are being given to individuals or in clinical trials against SARS-CoV-2. Objective: The aim of this study is to uncover the potential effects of Luteolin (Lut) as an inhibitor of SARS-CoV2 encoded proteins via utilizing computational tools. Methods: Molecular modelling to unfold the anti-SARS-CoV2 potential of Lut along with reference drugs namely remdesivir and nafamostat was performed by the use of molecular docking, molecular dynamic (MD) simulation, absorption, distribution, metabolism, excretion, toxicity (ADMET) and density functional theory (DFT) methods against the five different SARS-CoV-2 encoded key proteins and one human receptor protein. The chemical reactivity of Luteolin is done through prediction of HOMO-LUMO gap energy and other chemical descriptors analysis. Results: In the present study, Lut binds effectively in the binding pockets of spike glycoprotein (6VSB), ADP phosphatase of NSP3 (6W02), and RNA dependent RNA polymerase (7AAP) protein receptors with significant values of docking scores -7.00, -7.25, and -6.46 respectively as compared to reference drugs remdesivir and nafamostat. Conclusion: Thus, Lut can act as a therapeutic agent and is orally safe for human consumption as predicted by molecular modelling against SARS-CoV-2 in the treatment of COVID-19.
Keywords: molecular docking